Pentahelix Model Pengembangan Pariwisata: Modeling Talang Beautiful Tourism Development in Fajaresuk District. Pringsewu - Saputri, Fadillah Wahyu (Jurnal Kompetitif Bisnis, 2020)
The research objectives describe the implementation of the pentahelix model in Talang Indah tourism development in Pringsewu District. The theory uses the Pentahelix Model. Descriptive research type, qualitative approach. Informants were determined by using a purposive sampling technique with a sample of 10 informants consisting of the academy, business, community, government, and media Talang Indah. Secondary data sourced from data obtained from Disporpa (Department of Youth, Sports, and Tourism Pringsewu District) as well as parties or administrators of Talang Indah Fajaresuk. Data analysis using data reduction, data display, and conclusion drawing/verification, then validated by triangulation of sources. From the research it can be seen that the academy in Talang Indah Tourism has not played an active role in the development of tourism, businesses play a role in changing people's lives, the community has a high interest and influence on the development of Talang Indah Tourism, the government plays an important role in developing Talang Indah Tourism because it acts as a regulator and also plays a role as a controller, and the media play an active role in the development of Talang Indah Tourism as a provider of information, education, entertainment, and as a social controller. This study recommends that the community participates in preserving and preserving historical and cultural heritage, the government can make clear legal policy regulations and follow up on MOU agreements with large halls on the Talang Indah Tourism land, businesses can increase events to develop creativity, and the media can add promotion through the strength of the community built on social networks conducted to inform about Talang Indah Tourism. Keywords: Pentahelix, Development, Tourism.